HUBUNGAN ANTARA AKTIVITAS BERMAIN BULUTANGKIS DENGAN KECENDERUNGAN TERKENA TENNIS ELBOW DI GOR BULUTANGKIS DIRGANTARA KARTASURA - KUSUMAWARDANI, DHIAN (2010)

(untitled)
Injury is a risk whom every one, especially an athlete. Injury can happen because a crash (physical contact or fallen down). it can happen when an athlete do wrong movement, repeatedly movement for a while, over capacity of playing and equipments of sport unergonomic. Badminton activity had various movement types for example movement using arm. This movements if he did not control will injury. Tennis Elbow is including injuring elbow and many met at player tennis entangling hand and wrist over movement.The objective is aim to know the relation between badminton activities with possibility tennis elbow at Dirgantara badminton hall of Kartasura. Research method is using survey non experiment, research design with cross sectional approach, total sample are 125 responders, sampling method is totalizing sampling. Using test hypothesis is chi Square test with level confident 95%. Result of research shows chi Square test with p= 0,000. The conclusion is there is a relation between badminton activities with possibility tennis elbow at Dirgantara badminton hall of Kartasura